POTENTIAL EROSION FROM AGRICULTURAL LAND IN KENAGARIAN AIE DINGIN, SOLOK REQENSY - YENI, YUSMA; Hermon, MP, Dr. Dedi; , S.Si, M.Sc, Farida (Pendidikan Geografi, 2014)
ABSTRACTÂ Â This research was conducted in Kenagarian Aie Dingin Solok Regensy with the aim to describe the ( 1 ) Characteristics Soil in Agricultural Land in Kenagarian Aie Dingin Solok Regensy .( 2 ) To calculate the potential erosion from agricultural land. This study using a quantitative survey methods , data sources are the primary data and secondary data . The sampling technique is purposive sampling . Characteristics of land in the study area is the alluvialwithâs, andosol soil. Texture dusty clay loam soil , loam , silty clay . Flat - steep slope < 13-40 % . Long- short - long slope < 15-250 % . Agricultural land use mixedbetween , grass , rice paddy fields , and forests .The risk of erosion or the maximum amount of soil loss ( tons / ha / year ) is determined by using the equation USLE ( Universal Soil Loss Equation ) from Smith and Wischmeier ( 1978) The first sample has 17% slope, with 45 m slope length with mix of agricultural land use type. The potential erosian from the first sample is 280.27 tons / ha / year. Second sample has 18% slope, with 169 m slope length with mix of agricultural land use type. The potential erosian from the first sample is 954.02 tons / ha / year. Second sample has 20%Â  slope, with 170 m slope length with mix of agricultural land use type. The potential erosian from the first sample is 701.02 tons / ha / year Â Â Â Â Â Â Â Â Â Â